T. S. Eliot - Sharpe, Tony. author. aut Link
IX, 189 p.
Keywords: Part of a series which offers accounts of the literary careers of the most widely read British and Irish authors. This volume looks at T.S.Eliot and traces the professional, publishing and social contexts which shaped his writing.